An appraisal of the drivers of Norwegian spring‐spawning herring (Clupea harengus) recruitment. (30th October 2020) - Garcia, Théo; Planque, Benjamin; Arneberg, Per; Bogstad, Bjarte; Skagseth, Øystein; Tiedemann, Maik
Abstract: Norwegian spring‐spawning herring (NSSH, Clupea harengus ) is a key species in the food‐web and for fisheries in the north‐east Atlantic. NSSH has been the focus of many ecological and fisheries studies over decades and several hypotheses have been put forward to explain variations in its recruitment. We conducted an extensive literature review of the processes that have been hypothesized to control recruitment at age‐2 years. From this review, we constructed a conceptual model to represent how these processes are inter‐connected. We then evaluated several of these hypothesized processes using quantile regression modelling and the most recent available data series as input. Most of the hypotheses were not supported by our analyses. Only two hypotheses were supported: the top‐down control of herring larval stage by Atlantic mackerel ( Scomber scombrus ) and the positive effect of temperature on recruitment. For the latter the interpretation of the results is nevertheless ambiguous when the latest years (1998–2018) of observations are included, as the correlation then changes from positive to negative. Furthermore, when retesting the hypotheses on age‐2 years estimates, we observe a benefitting effect of a consistent strong forcing of the Norwegian Coastal Current and a possible positive effect of the NSSH spawning stock on recruitment. How much these hypotheses can be used to make predictions about future recruitment of herring remains to be tested but based on our results, the relatively short time series available and the dispersion of the observations around the regression models, we can anticipate that such predictions would have limited use for the purpose of fisheries assessment and management.